Constructing a Strongly Absorbing Low‐Bandgap Polymer Acceptor for High‐Performance All‐Polymer Solar Cells. (19th September 2017) - Zhang, Zhi‐Guo; Yang, Yankang; Yao, Jia; Xue, Lingwei; Chen, Shanshan; Li, Xiaojun; Morrison, William; Yang, Changduk; Li, Yongfang
Abstract: All‐polymer solar cells (all‐PSCs) offer unique morphology stability for the application as flexible devices, but the lack of high‐performance polymer acceptors limits their power conversion efficiency (PCE) to a value lower than those of the PSCs based on fullerene derivative or organic small molecule acceptors. We herein demonstrate a strategy to synthesize a high‐performance polymer acceptor PZ1 by embedding an acceptor–donor–acceptor building block into the polymer main chain. PZ1 possesses broad absorption with a low band gap of 1.55 eV and high absorption coefficient (1.3×10 5 cm −1 ). The all‐PSCs with the wide‐band‐gap polymer PBDB‐T as donor and PZ1 as acceptor showed a record‐high PCE of 9.19 % for the all‐PSCs. The success of our polymerization strategy can provide a new way to develop efficient polymer acceptors for all‐PSCs.